Reporting of central airway obstruction on radiology reports and impact on bronchoscopic airway interventions and patient outcomes - Harris, Kassem (Ther Adv Respir Dis, 2015)
BACKGROUND: Central airway obstruction (CAO) is a serious condition that affects patients with both benign and malignant diseases. Timely recognition of CAO is crucial for prompt intervention aimed at improving the symptoms and quality of life of these patients. The aim of this study is to evaluate the formal radiology reporting of CAO and its impact on patients’ outcomes. METHODS: The medical records of patients who underwent advanced therapeutic bronchoscopy for CAO from August 2013 to September 2014 were retrospectively reviewed. Three researchers each reviewed 14 of the 42 formal radiology reports that were performed at 16 different medical and radiology centers. Patient characteristics were reported as means, medians, and standard deviations for continuous variables, and as frequencies and relative frequencies for categorical variables. RESULTS: Out of 42 patients who underwent advanced bronchoscopy for planned therapeutic intervention, only 30 had radiology and pulmonology concordance about the airway findings of CAO. This is an agreement rate of 71.4% [95% confidence interval (CI): 56.7–83.3%] or a disagreement rate of 28.6% (95% CI: 16.7–43.3%). The radiology reports did not mention 31% of CAO on CT scans. The median time from CT imaging to bronchoscopy was significantly longer in patients with CAO not reported by the radiologists (21 versus 10 days; p = 0.011). Most patients improved postoperatively with no significant difference between the two groups. CONCLUSIONS: Findings of CAOs were not described in a significant proportion of radiology reports. This results in significant delay in bronchoscopic airway management.